< Home

Chapter 2

2.1 - Set Theory

Definition (Primitive term)

Primitive term is a term without a formal def

Definition (Axiom)

Result or idea we accept without formal proof

axiom (1)

There is a set

axiom (2)

For every object xx and set SS, we can determine if xx is an element of SS or not.

Definition (Containment)

Let AA and BB be sets. Then, AA is contained in BB, written ABA \subseteq B iff xA,xB\forall x \in A, x \in B. Otherwise, we write A⊈BA \not\subseteq B.

Example

Consider the following model:

  1. The objects under consideration are the first five lowercase letters of the alphabet.
  2. There is a set S={a,b,c,d,e}S = \{ a, b, c, d, e \}.

This model satisfies Axioms 1 & 2

(Figure 2.2 in the book)

Example

Consider the following model:

  1. The objects under consideration are the first six lowercase letters of the alphabet.
  2. There is a set S={a,b,c,d,e}S = \{ a, b, c, d, e \}.

This model satisfies Axioms 1 & 2

(Figure 2.2 in the book)

2.2 - Axiom of Specification

axiom (Axiom of Specification)

If SS is a set and p()p(\bullet) is an open sentence for the elements of SS, then the collection of all elements xSx \in S that satisfy p(x)p(x) is a set, too.

Proposition (Empty Set)

There is a set that contains no elements.

Proof (by construction)

By A1, we know a set SS exists. We also know that the open sentence p(x)=[xSx∉S]p(x) = [x \in S \land x \not\in S] is false for all objects.

By A3, the collection B={x:p(x)}B = \{ x : p(x) \} of all elements xx that satisfy p(x)p(x) is a set also. Since p(x)p(x) is false xS\forall x \in S, BB has no elements.

\square

Definition (Empty Set)

We call the set having no elements the empty set. Denoted as \emptyset.

Definition ()

A set S\mathcal{S} whose elements are sets too is called a family of sets.

Proposition (Intersection)

Let C\mathcal{C} be a non-empty family of sets. Then there is a set I\mathcal{I} so that an object xIx \in \mathcal{I} iff cC\forall c \in \mathcal{C} we have that xCx \in \mathcal{C}.

Proof (by construction)

Let C\mathcal{C} be a family of sets. CC\forall C \in \mathcal{C}, xCx \in C is an open sentence for the elements of C\mathcal{C}. Let C0C_0 be an arbitrary set in C\mathcal{C}. By the axiom of specification, I={xC0:CC,xC}\mathcal{I} = \{ x \in C_0 : \forall C \in \mathcal{C}, x \in C \} is a set and it contains the elements that are in every set CCC \in \mathcal{C}.

\square

Definition (Intersection)

Let C\mathcal{C} be a family of sets. The set of elements xx so that xCCCx \in C \forall C \in \mathcal{C} is called the intersection of C\mathcal{C} and is denoted C\bigcap \mathcal{C}.

If AA and BB are sets, their intersection is written ABA \cap B.

Proposition

Let C\mathcal{C} be a family of sets and CCC \in \mathcal{C}. Then CC\bigcap \mathcal{C} \subseteq C.

Definition (disjoint)

Let C\mathcal{C} be a family of sets. If C=\bigcap \mathcal{C} = \emptyset, then the family of sets is called disjoint.

Example

Let C={A,B,C}\mathcal{C} = \{A, B, C\} where A={1,2}A = \{1, 2\}, B={2,3,4}B = \{2, 3, 4\}, C={3,4,5}C = \{3, 4, 5\}

  1. AB={2}A \cap B = \{ 2 \}
  2. BC={3,4}B \cap C = \{ 3, 4 \}
  3. C=\bigcap \mathcal{C} = \emptyset

Proposition

Let AA and BB be sets. Then there is a set that contains all elements of AA that are not in BB.

Proof (by construction)

Let AA and BB be sets. Let p(x)={xAx∉B}p(x) = \{ x \in A \land x \not\in B \} be an open sentence for the elements of AA. Then the set of elements of AA that are not in BB exists and is {xA:x∉B}\{ x \in A : x \not\in B\}.

\square

Definition (Relative Compliment)

Let AA and BB be sets. Then we call the relative compliment, or compliment of BB in AA, the set AB={xA:x∉B}A \setminus B = \{x \in A : x \not\in B\}.

2.3 -- Axiom of Extension

axiom (Axiom of Extension)

Two sets are equal iff they have the same elements. That is if AA, BB are sets, A=B    x,xA    xBA = B \iff \forall x, x \in A \iff x \in B

sidenote (def of containment)

ABA \subseteq B iff xA    xBx \in A \implies x \in B

Theorem

A=B    ABBAA = B \iff A \subseteq B \land B \subseteq A

Proof

(    \implies) Suppose A=BA = B. Then, by definition, xA    xBx \in A \implies x \in B and xB    xAx \in B \implies x \in A.

Then by definition of subsets, ABA \subseteq B and BAB \subseteq A.

(    \impliedby) Suppose ABBAA \subseteq B \land B \subseteq A. Let xAx \in A be an arbitrary but fixed. Since ABA \subseteq B, we have xBx \in B, thus xA    xBx \in A \implies x \in B. Now, let xBx \in B be arbitrary but fixed. Since BAB \subseteq A, xAx \in A, thus xB    xAx \in B \implies x \in A. Therefore, xA    xBx \in A \iff x \in B and by definition, A=BA = B.
\square

This tells us that we can use mutual containment, ABBA    A=BA \in B \land B \in A \implies A = B, to prove equality.

Theorem

AB=BAA \cap B = B \cap A

Proof (by mutual containment)

  1. Prove ABBAA \cap B \subseteq B \cap A

Let xABx \in A \cap B be arbitrary but fixed.
Then xAxBx \in A \land x \in B.
Thus, xBxAx \in B \land x \in A.
Therefore, xBAx \in B \cap A and ABBAA \cap B \subseteq B \cap A.

  1. Prove BAABB \cap A \subseteq A \cap B

Let xBAx \in B \cap A be arbitrary but fixed.
    xBxA\implies x \in B \land x \in A.
    xAxB\implies x \in A \land x \in B.
    xAB\implies x \in A \cap B
    BAAB\implies B \cap A \subseteq A \cap B.

Thus, by M.C., AB=BAA \cap B = B \cap A.
\square

Theorem

Let A,B,CA, B, C be sets, then A(BC)=(AB)CA \cap (B \cap C) = (A \cap B) \cap C.

Prove as exercise.

Theorem

Let A,BA, B be sets. Then AB    AB=AA \subseteq B \iff A \cap B = A.

(    \implies) Let ABA \subseteq B. To show AB=AA \cap B = A, we will use mutual containment.

Let xABx \in A \cap B be ABF. By def, xAx \in A, thus ABAA \cap B \subseteq A.

Let xAx \in A be ABF. Since ABA \subseteq B, xBx \in B. As xAxBx \in A \land x \in B, xABx \in A \cap B and AABA \subseteq A \cap B. Thus, AB=AA \cap B = A.

(    \impliedby) Let AB=AA \cap B = A. Let xAx \in A be ABF. Since A=ABA = A \cap B, xABx \in A \cap B. Then, xAxBx \in A \land x \in B. Thus, xBx \in B and ABA \subseteq B. Therefore, AB    AB=AA \subseteq B \iff A \cap B = A
\square

Theorem

A(AB)=ABA \setminus (A \setminus B) = A \cap B

Proof

Let xA(AB)x \in A \setminus (A \setminus B) be ABF.
    xAx∉AB\implies x \in A \land x \not\in A \setminus B
    xA¬[xAx∉B]\implies x \in A \land \neg [x \in A \land x \not\in B]     xA[x∉AfalsexB]\implies x \in A \land [\underbrace{x \not\in A}_\text{false} \land x \in B]
    xAxB\implies x \in A \land x \in B
    xAB\implies x \in A \cap B
Thus, A(AB)ABA \setminus (A \setminus B) \subseteq A \cap B.

Let xABx \in A \cap B be ABF.
    xAxB\implies x \in A \land x \in B
    xA[x∉AfalsexB]\implies x \in A \land [\underbrace{x \not\in A}_\text{false} \land x \in B]
    xA¬[xAx∉B]\implies x \in A \land \neg [x \in A \land x \not\in B]     xAx∉AB\implies x \in A \land x \not\in A \setminus B
Thus, xA(AB)x \in A \setminus (A \setminus B).
\square

2.4 -- Axiom of Unions

For every family C\mathcal{C} of sets, there exists a set whose elements are all elements that belong to at least one element of the family denoted C\bigcup \mathcal{C} or ABA \cup B

Proposition

let C\mathcal{C} be a family of sets and CCC \in \mathcal{C}. Then C is a subset of C\bigcup \mathcal{C}.

Proof

Let xCx \in C be ABF. By the axiom of unions, xCx \in \bigcup \mathcal{C}. Thus, CCC \subseteq \bigcup \mathcal{C}.
\square

Theorem

AB=BAA \cup B = B \cup A

% TODO: FINISH NOTES FROM NOTEPAD

Theorem (DeMorgan's Laws)

  1. A(BC)=(AB)(AC)A \setminus (B \cup C) = (A \setminus B) \cap (A \setminus C)

Proof (algebraic)

A(BC)={x:xA(BC)}={x:xAx∉(BC)}={x:xAx∉Bx∉C}={x:(xAxA)x∉Bx∉C}={x:(xAx∉B)(xAx∉C)}={x:x(AB)x(AC)}={x:x((AB)(AC))} \begin{align} A \setminus (B \cup C) &= \{ x : x \in A \setminus (B \cup C) \} \\ &= \{ x : x \in A \land x \not\in (B \cup C) \} \\ &= \{ x : x \in A \land x \not\in B \land x \not\in C \} \\ &= \{ x : (x \in A \land x \in A) \land x \not\in B \land x \not\in C \} \\ &= \{ x : (x \in A \land x \not\in B) \land (x \in A \land x \not\in C) \} \\ &= \{ x : x \in (A \setminus B) \land x \in (A \setminus C) \} \\ &= \{ x : x \in ((A \setminus B) \cap (A \setminus C)) \} \end{align} \square

  1. A(BC)=(AB)(AC)A \setminus (B \cap C) = (A \setminus B) \cup (A \setminus C)

Definition (Symmetric Difference)

The symmetric difference AB=(AB)(BA)A \triangle B = (A \setminus B) \cup (B \setminus A)

ex: Prove AB=(AB)(AB)A \triangle B = (A \cup B) \setminus (A \cap B)

2.5 -- Axiom of Powers; Relations and Functions

axiom (Axiom of powers)

For every set SS, there exists a set P(S)\mathcal{P}(S) called the "power set" of SS whose elements are all subsets of SS.

Example

Let S={a,b}S = \{a, b\}

P(S)={,{a},{b},{a,b}}\mathcal{P}(S) = \{\emptyset, \{a\}, \{b\}, \{a, b\}\}

Let S=S = \emptyset

P(S)={}\mathcal{P}(S) = \{\emptyset\}

If S=n|S| = n, then P(S)=2n|\mathcal{P}(S)| = 2^n

Theorem

Let {a,b}\{a, b\} and {c,d}\{c, d\} be sets with one or two elements (aa can be equal to bb). Then {{a},{a,b}}={{c},{c,d}}\{\{a\}, \{a, b\}\} = \{\{c\}, \{c, d\}\} holds iff a=ca = c and b=db = d.

Proof

(    \impliedby) Suppose a=ca = c and b=db = d. Then {{a},{a,b}}={{c},{c,d}}\{\{a\}, \{a, b\}\} = \{\{c\}, \{c, d\}\}.

(    \implies) Suppose {{a},{a,b}}={{c},{c,d}}\{\{a\}, \{a, b\}\} = \{\{c\}, \{c, d\}\}. By the axiom of extension, they have exactly the same elements. Then we have two disjoint cases.

  1. {a}={c,d}\{ a \} = \{ c, d \}. By the axiom of extension, a=c=da = c = d. This implies {{c}}={{c},{c,d}}={{a},{a,b}}    c=a=b\{ \{ c \} \} = \{ \{ c \}, \{ c, d \} \} = \{ \{ a \}, \{ a, b \} \} \implies c = a = b Thus, a=b=c=da = b = c = d, i.e. a=cb=da = c \land b = d.

  2. {a}{c,d}\{a\} \neq \{c,d\}. Then, {a}={c}\{ a \} = \{ c \}. Then, a=ca = c. Since {{a},{a,b}}={{c},{c,d}}\{ \{ a \}, \{a,b\}\} = \{ \{ c \}, \{ c, d \} \} and {a}{c,d}\{a\} \neq \{c,d\}, we have {a,b}={c,d}\{a,b\} = \{c,d\}. cdc \neq d, therefore b=db = d. Thus, a=cb=da = c \land b = d.

\square

Definition (Ordered Pair)

Let AA and BB be sets with aAbBa \in A \land b \in B. Then the ordered pair (a,b)={{a},{a,b}}(a, b) = \{ \{a\}, \{a, b\} \}

Definition (Cartesian Product)

Let AA, BB be sets. The Cartesian product is defined as A×B={(a,b):aAbB}A \times B = \{ (a, b) : a \in A \land b \in B \}

Definition

A subset ~A×B\char`~ \subseteq A \times B is also called a relation from AA to BB.

Example

A={a,b,c}B={1,2,3}A×B={(a,1),(a,2),(a,3),(b,1),(b,2),(b,3),(c,1),(c,2),(c,3)} \begin{align} A &= \{a, b, c\} \\ B &= \{1, 2, 3\} \\ A \times B &= \{(a,1), (a,2), (a,3), (b,1), (b,2), (b,3), (c,1), (c,2), (c,3)\} \\ \end{align}

notation

If an element, say (a,1)(a, 1) \in \sim, we write a1a \sim 1. If an element, say (b,1)∉(b, 1) \not\in \sim, we write b≁1b \not\sim 1. We also write the relation as :AB\sim: A \to B.

Definition (Domain, Range)

Let :AB\sim: A \to B be a relation.

Domain: dom()={aA:bB:ab}dom(\sim) = \{ a \in A: \exists b \in B : a \sim b \}
Range: rng()={bB:aA:ab}rng(\sim) = \{ b \in B: \exists a \in A : a \sim b \}

Example

A={1,2,3,4}A = \{ 1, 2, 3, 4 \}
B={2,5,6,7}B = \{ 2, 5, 6, 7 \}
let :{(1,2),(2,2),(3,5)}\sim: \{(1, 2), (2, 2), (3, 5)\}
dom()={1,2,3}dom(\sim) = \{ 1, 2, 3 \}
rng()={2,5}rng(\sim) = \{ 2, 5 \}

Example

Let \sim be <<. This is a relation.

If a<ba < b, then aba \sim b, i.e. (a,b)(a, b) \in \sim

A={1,2,8,9}A = \{ 1, 2, 8, 9 \}
B={2,5,1,10}B = \{ 2, 5, 1, 10 \}
:{(1,2),(1,5),(1,10),(2,5),(2,10),(8,10),(9,10)}\sim: \{ (1, 2), (1, 5), (1, 10), (2, 5), (2, 10), (8, 10), (9, 10) \}

Definition

Let AA and BB be sets and f:ABf : A \to B be a relation from AA to BB. Then ff is a function iff the following hold:

Functions are also called mappings.

We also write f(a)=bf(a) = b if (a,b)f(a, b) \in f.

Definition

Let AA, BB be sets and f:ABf: A \to B be a function.

  1. ff is injective iff x,yA:xy    f(x)f(y)\forall x, y \in A: x \neq y \implies f(x) \neq f(y)
  2. ff is surjective iff yBxA:f(x)=y\forall y \in B \exists x \in A : f(x) = y

If a function is both injective AND surjective, then it is called bijective.

Proposition

Let AA, BB be sets. Let f:ABf: A \to B be a function. Then ff is injective iff x,yA\forall x, y \in A we have that f(x)=f(y)    x=yf(x) = f(y) \implies x = y.

Example

Let f:R{2}R:f(x)=4x+3x2f: \R \setminus \{ 2 \} \to \R : f(x) = \frac{4x + 3}{x-2} (we'll pretend R\R exists)

Prove it is injective:

Let f(x)=f(y)f(x) = f(y) : 4x+3x2=4y+3y2\frac{4x+3}{x-2} = \frac{4y+3}{y-2} (4x+3)(y2)=(4y+3)(x2)4xy8x+3y6=4xy8y+3x68x+3y=8y+3x11y=11xy=x \begin{align} (4x+3)(y-2) &= (4y+3)(x-2) \\ 4xy - 8x + 3y - 6 &= 4xy - 8y + 3x - 6 \\ 8x + 3y &= 8y + 3x \\ 11y &= 11x \\ y &= x \\ \end{align}

Definition

Let AA, BB, CC be sets and g:ABf:BCg : A \to B \land f: B \to C be functions. The composition is defined:
fg={(a,c)A×C:[bB:g(a)=bf(b)=c]} f \circ g = \{ (a, c) \in A \times C : [ \exists b \in B : g(a) = b \land f(b) = c ] \}

fg=f(g(a))=f(b)=c f \circ g = f(g(a)) = f(b) = c

Example

A={a,b,c,d}B={α,β,γ,ω}C={1,2,3}g={(a,β),(b,ω),(c,γ),(d,α)}:ABf={(α,3),(β,1),(γ,3),(ω,2)}:BCfg={(a,1),(b,2),(c,3),(d,3)} \begin{align} A &= \{ a, b, c, d \} \\ B &= \{ \alpha, \beta, \gamma, \omega \} \\ C &= \{ 1, 2, 3 \} \\ g &= \{(a, \beta), (b, \omega), (c, \gamma), (d, \alpha)\}: A \to B \\ f &= \{ (\alpha, 3), (\beta, 1), (\gamma, 3), (\omega, 2) \}: B \to C \\ f \circ g &= \{ (a, 1), (b, 2), (c, 3), (d, 3) \} \end{align}

Definition (Identity Function)

Let AA be a set idA={(a,a)A×A:aA}id_A = \{ (a, a) \in A \times A : a \in A \} is called the identity function on AA.

Example

Let f:ABf: A \to B and g:CAg: C \to A be functions. Find fidAf \circ id_A and idAgid_A \circ g.

  1. f:AB:f(a)=bf: A \to B : f(a) = b
    idA:AA:idA(a)=aid_A : A \to A : id_A(a) = a
    fidA=f(idA(a))=f(a)=bf \circ id_A = f(id_A(a)) = f(a) = b
    fidA=ff \circ id_A = f

  2. Exercise

Definition (inverse)

let AA, BB be sets and let f:ABf: A \to B be a function. The function g:BAg: B \to A is called the inverse of ff iff fg=idBf \circ g = id_B and gf=idAg \circ f = id_A.

Example

A={α,β,γ}B={a,b,c}idA={(α,α),(β,β),(γ,γ)}idB={(a,a),(b,b),(c,c)} \begin{align} A &= \{ \alpha, \beta, \gamma\} \\ B &= \{ a, b, c \} \\ id_A &= \{ (\alpha, \alpha), (\beta, \beta), (\gamma, \gamma)\} \\ id_B &= \{ (a, a), (b, b), (c, c) \} \\ \end{align}

let f={(α,b),(β,a),(γ,c)}f = \{(\alpha, b), (\beta, a), (\gamma, c) \}
let g={(a,β),(b,γ),(c,α)}g = \{(a, \beta), (b, \gamma), (c, \alpha) \}

fg=f(g)f(g(a))=f(β)=af(g(b))=f(γ)=cNot inversesfg=f(g)={(a,a),(b,c) \begin{align} f \circ g &= f(g) \\ f(g(a)) &= f(\beta) = a \\ f(g(b)) &= f(\gamma) = c &&& \text{Not inverses} \\ f \circ g &= f(g) = \{ (a, a), (b, c) \end{align}

Example

A={α,β,γ}B={a,b,c}idA={(α,α),(β,β),(γ,γ)}idB={(a,a),(b,b),(c,c)} \begin{align} A &= \{ \alpha, \beta, \gamma\} \\ B &= \{ a, b, c \} \\ id_A &= \{ (\alpha, \alpha), (\beta, \beta), (\gamma, \gamma)\} \\ id_B &= \{ (a, a), (b, b), (c, c) \} \\ \end{align}

let f={(α,b),(β,a),(γ,c)}f = \{(\alpha, b), (\beta, a), (\gamma, c) \}
let g={(a,β),(b,α),(c,γ)}g = \{(a, \beta), (b, \alpha), (c, \gamma) \}

f(g(a))=f(β)=af(g(b))=f(α)=bf(g(c))=f(γ)=cfg=f(g)={(a,a),(b,b),(c,c)}=idBgf=g(f)={(α,α),(β,β),(γ,γ)}=idA \begin{align} f(g(a)) &= f(\beta) = a \\ f(g(b)) &= f(\alpha) = b \\ f(g(c)) &= f(\gamma) = c \\ f \circ g &= f(g) = \{ (a, a), (b, b), (c, c) \} = id_B \\ g \circ f &= g(f) = \{ (\alpha, \alpha), (\beta, \beta), (\gamma, \gamma) \} = id_A \\ \end{align}

Definition

Two sets AA, BB are equivalent iff \exists a bijective function f:ABf: A \to B.

Theorem

If XX is a set, then XX is not equivalent to P(X)P(X)

Proof

SFAC, \exists a bijective function f:XP(X)f: X \to P(X).

B={xX:x∉f(x)}B = \{ x \in X : x \not\in f(x) \} -- This is the set of elements xx that are mapped to a subset of XX for which xx is not a member.

By the axiom of specification, BB is a set and BXB \subseteq X. Then, BP(X)B \in P(X). Since ff is surjective, bX:f(b)=B\exists b \in X : f(b) = B. If bBb \in B, then b∉f(b)=Bb \not\in f(b) = B, thus b∉Bb \not\in B, but then bBb \in B. Contradiction.

Thus, no bijection exists and the sets are not equivalent.
\square

Definition (Indexed Family of Subsets)

let XX be a set. An indexed family of subsets SiS_i of XX is denoted {Si}iI\{ S_i \}_{i \in I} where it is understood that there is a function from II to P(X)P(X) that maps each iIi \in I to SiS_i. If {Si}iI\{S_i\}_{i \in I} is an indexed family of sets, the union is iISi={xX:[iI:xSi]}\bigcup_{i \in I}S_i = \{x \in X : [\exists i \in I : x \in S_i ]\} and the intersection iISi={xX:[iI:xSi]}\bigcap_{i \in I}S_i = \{x \in X : [\forall i \in I : x \in S_i ]\}

Definition

Let XX be a set. Define V0(X)=XV_0(X) = X and for each nNn \in \N, define Vn(X)=Vn1P(Vn1(X))V_n(X) = V_{n-1} \cup P(V_{n-1}(X))

Example

X={a,b,c}V0(X)={a,b,c}V1(X)=V0P(V0)={{a,b,c},{,{a},{b},{c},..P(X)}} \begin{align} X &= \{ a, b, c \} \\ V_0(X) &= \{ a, b, c \} \\ V_1(X) &= V_0 \cup P(V_0) = \{ \{ a, b, c \}, \{\emptyset, \{a\}, \{b\}, \{c\}, \mathtt{..P(X)} \} \} \\ \end{align}

V(X)=nN0Vn(C)V(X) = \cup_{n \in N_0}V_n \in (C) is called the superstructure of XX.

2.6 -- The Axiom of Infinity and the Natural Numbers

axiom

There is a set II that contains \emptyset and an element and for each aIa \in I the set a{a}Ia \cup \{ a \} \in I also.

I\emptyset \in I
{}I\emptyset \cup \{ \emptyset \} \in I => {}I\{ \emptyset \} \in I
{}{{}}I\{ \emptyset \} \cup \{ \{ \emptyset \} \} \in I => {,{}}I\{ \emptyset, \{ \emptyset \}\} \in I

I={,{}{,{}}{,{},{,{}}}} \begin{align} I = \{ \\ & \emptyset, \\ & \big\{ \emptyset \big\} \\ & \big\{ \emptyset, \{ \emptyset \} \big\} \\ & \big\{ \emptyset, \{ \emptyset \}, \{ \emptyset, \{ \emptyset \} \} \big\} \\ & \cdots \} \end{align}

let 1={}1 = \{ \emptyset \}
and nI\forall n \in I, let n=n{n}n' = n \cup \{n\}

Definition (successor set)

We call SIS \subseteq I a successor set iff ∉S\emptyset \not\in S, 1S1 \in S, and nS,nS\forall n \in S, n' \in S

The Peano Axioms

There is a set, denoted N\N called the natural numbers, such that:

  1. \exists a special element, 1N1 \in \N
  2. nN,nN\forall n \in \N, \exists n' \in \N, called the successor of nn.
  3. 11 is not the successor of any element nNn \in \N.
  4. Principle of Induction: If SNS \subseteq N is such that 1S1 \in S and nS\forall n \in S, we have nSn' \in S, then S=NS = \N.
  5. n,mN\forall n, m \in \N, if m=nm' = n', then m=nm = n

Notice: All successor sets are subsets of II
    \implies every successor set P(I)\in P(I). By the axiom of specification, \exists a subset SP(I)\mathcal{S} \subseteq P(I) whose elements are all the successor sets.
Let N=S\N = \bigcap \mathcal{S}

Proof

  1. We need to prove 1N1 \in \N. Every successor set SS contains 11 as an element, thus 1S=N1 \in \bigcap \mathcal{S} = \N.
  2. Now, we need to prove nN\forall n \in \N, nNn' \in \N. Let nNn \in \N be ABF.
    Since, nNn \in \N, nSn \in \bigcap \mathcal{S}, thus SS,nS\forall S \in \mathcal{S}, n \in S. By definition of successor sets, nSSn' \in S \forall S, thus nS=Nn' \in \bigcap \mathcal{S} = \N.
  3. We need to show that 11 is not the successor of any element of N\N. SFAC that 1=x1 = x' for some xNx \in \N. Then, 1=x=x{x}1 = x' = x \cup \{ x \}. BUt we defined, 1={}1 = \{ \emptyset \}. Then {}=x{x}    x=\{ \emptyset \} = x \cup \{ x \} \implies x = \emptyset. But we defined SS so that the ∉S\emptyset \not\in S. Contradiction. Thus, 11 is not a successor.
  4. We must prove that SNS \subseteq \N and 1S1 \in S and nS:nS\forall n \in S : n' \in S, then S=NS = \N. Let SS be ABF subset of N\N so that 1S1 \in S and nS:nS\forall n \in S : n' \in S.
    We will prove S=NS = \N by mutual containment. Clearly, SNS \subseteq N.
    We defined N=S\N = \bigcap \mathcal{S}, thus SS,NS\forall S \in \mathcal{S}, \N \subseteq S. Therefore, S=NS = \N.
  5. Se must prove n,mN\forall n, m \in \N with m=nm' = n', we have m=nm = n. First, we prove nN\forall n \in \N, every element of nn is a subset of nn. Let S={nN:[mn:mn]}S = \{ n \in \N : [ \forall m \in n : m \subseteq n ] \}. This is equivalent to S=NS = \N. Trivially, 1S1 \in S. Let nSn \in S. To prove nSn' \in S, recall that n=n{n}n' = n \cup \{ n \}. Hence, if mnm \in n', then mn{n}m \in n \cup \{ n \}. Thus, m=nm = n or mnm \in n. If m=nm = n, since nnn \subseteq n', mnm \subseteq n' and nSn' \in S. If mnm \in n, because nSn \in S, mnnm \subseteq n \subseteq n'. Thus, nSn' \in S and by Principle of Induction, S=N    S = \N \implies if mnm \in n, mnm \subseteq n.
    Now, let m=nm' = n'. Then, m=m{m}=n=n{n}m' = m \cup \{ m \} = n' = n \cup \{ n \}. SFAC that mnm \neq n. Then {m}{n}\{ m \} \neq \{ n \}. Which implies mnnmm \in n \land n \in m, but then mnnmm \subseteq n \land n \subseteq m and n=mn = m. Contradiction. Therefore, if m=nm' = n', then m=nm = n.